Litterær shamanisme i Kongebøgerne – sagaen om Elias og Elisa - Nielsen, Flemming A.J. (Dansk Teologisk Tidsskrift, 2015)
The Saga of Elijah and Elisha (1 Kgs 16:29 – 2 Kgs 13:25) deals with the history of the cult of Ba’al in Biblical Israel. Its nucleus is a mosaic of 35 episodes containing several versions of the biographies of Elijah and Elisha who are atypical Old Testament prophets belonging to a select circle of “men of God”. Their saga supplements and comments on the greater story of Biblical Israel, and it is argued that there is an affinity between them and the shamans known in particular from the Arctic world and the aboriginal peoples of the Americas. Definitions of prophets and shamans are briefly discussed, and the kind of shamanism associated with Elijah and Elisha is described and named literary shamanism.